2022
DOI: 10.25139/jsk.v6i1.3772
|View full text |Cite
|
Sign up to set email alerts
|

Music streaming dalam industri musik era industri 4.0

Abstract: Industrial era 4.0 shows that all human activities will be connected and dominated by digital media. Creativity and new ideas to innovate technology are the keys of this era. For example in the music industry 4.0, which develops music streaming technology products, trying to attract a lot of millennials generation. In the context of Indonesia, Langit Musik as a local product competes with Spotify as an international product. Therefore, through this literature review-based research and interview with some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Evidenced by research conducted by Andry & Tjee (2019) which found that most students prefer to listen to music through Spotify premium, because of the good sound quality and can also download songs legally because they do not violate the copyright that has been represented by this Spotify platform. In addition, Spotify also has the main advantages of a simple and elegant appearance, the song genre category and song collection are quite rich, especially international Western songs, besides that it can also personalize songs, there is a Podcast feature for amateurs or beginners, superior in synchronization, can share it to social media, and also the premium subscription price is relatively affordable (Amanda, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Evidenced by research conducted by Andry & Tjee (2019) which found that most students prefer to listen to music through Spotify premium, because of the good sound quality and can also download songs legally because they do not violate the copyright that has been represented by this Spotify platform. In addition, Spotify also has the main advantages of a simple and elegant appearance, the song genre category and song collection are quite rich, especially international Western songs, besides that it can also personalize songs, there is a Podcast feature for amateurs or beginners, superior in synchronization, can share it to social media, and also the premium subscription price is relatively affordable (Amanda, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…This allows them to build networks and gain support from fellow artists and their fans. This development has replaced the traditional model centered around art institutions such as record labels, film studios, or art galleries (Amanda, 2022). The younger generation now has direct access to share and distribute their works through social media platforms without relying on third-party approval or support.…”
Section: The Impact Of Social Media On the Transformation Of Cultural...mentioning
confidence: 99%
“…Premium is a service that gives full access, free advertisement, and music downloads so that users can access the application without an internet connection (Masdaner & Ruliana, 2021). (Amanda, 2022) argued that premium service can cause user' satisfaction because premium service can give many features and advantages. Premium service can impact user satisfaction, so Spotify should be involved and increase its services.…”
Section: Introductionmentioning
confidence: 99%